IMPLEMENTASI PROGRAM PESANTREN RAMAH ANAK DALAM PEMBINAAN AKHLAK SANTRI DI PERGURUAN ISLAM AR-RISALAH PADANG - Sumiati Gusri; Martin Kustati; Bashori Bashori (CV. Adiba Aisha Amira, 2025)
This study is motivated by the importance of implementing the concept of a child-friendly pesantren as a strategy for moral development aligned with Islamic values and students’ developmental needs. The purpose of this research is to describe the implementation of the child-friendly pesantren program in fostering students’ morals at Ar-Risalah Islamic Institute Padang. This study employed a qualitative descriptive approach using observation, interviews, and documentation techniques. The results show that the child-friendly pesantren program is implemented through habituation, exemplary behavior, and humanistic communication between teachers, dormitory mentors, and students. The implementation of this program successfully nurtures students’ noble character, discipline, and empathy. The study concludes that the success of moral development in pesantren is strongly influenced by a child-friendly culture integrated into all aspects of pesantren life.